DAMPAK PENGUASAAN INFORMASI, PEMBELAJARAN ORGANISASI, DAN KOMITMEN PEGAWAI TERHADAP Kemampuan kerja SERTA IMPLIKASINYA PADA PENINGKATAN KINERJA PEGAWAI KANTOR PERTANAHAN PROVINSI ACEH - Arinaldi Arinaldi; Amri Amri; Nurdasila Darsono (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACTThe purpose of this study was to determine the impact of the mastery of information, organizational learning, and employee commitment to the completion of the work and its implications on improving the performance of employees land office Aceh province. The method chosen to analyze the data of this research is Structural Equation Model (SEM) using software Partial Least Square (PLS). Based on the analysis that has been done through observation and secondary data, it can be concluded that the mastery of information, organizational learning, employee commitment, completion of work, and increase employee performance is good, the first hypothesis is accepted. From the research that has been done can be concluded that the hypothesis that the mastery of information, organizational learning, and commitment of employees simultaneously and partially on the settlement of employee jobs can be accepted, with a value of 3.474 for the simultaneous influence employees' commitment to the completion of the work; 5.958 to influence organizational learning simultaneously on completion of the work; and 6.847 to influence the control information simultaneously on completion of the work. As for the effect of the partial mastery of information on the completion of work at 37.729, influence organizational learning partially on completion of the job amounted to 18.693, and influence employee commitment partially to the completion of the job amounted to 7.597. From the research that has been done can be concluded that the hypothesis that the mastery of information, organizational learning, and employee commitment influence simultaneously and partially on employee performance is acceptable, with a value of 2.191 for the simultaneous influence employee commitment to performance; 13.601 for the simultaneous influence of organizational learning on performance; and 2,747 for the mastery of information simultaneously influence on performance. As for the effect of a partial mastery of information on the performance of 19.561; the effect of organizational learning partially on the performance of 126.332; and influence employee commitment partially on the performance of 34.238. From the research that has been done can be concluded that the hypothesis that the completion of the work affect the performance is acceptable, with a value of t-statistic for at 49.015. From the research that has been done can be concluded that the hypothesis that the mastery of information, organizational learning and employee commitment influence simultaneously and partially on the performance of employees through the completion of the work is acceptable, with a value of 3,266 to influence control of information on employee performance through completion of the job simultaneously; 3.483 for organizational learning influence on employee performance through the completion of jobs simultaneously; and 3,103 to influence employees' commitment to employee performance through the completion of jobs simultaneously. As for the effect of a partial mastery of information on employee performance through completion of the job amounted to 7.687; the influence of organizational learning on the job performance of employees through partial settlement of 5.666; and influence employees' commitment to employee performance through partial completion of the work amounted to 6.975.Keywords : mastery of information, organizational learning, employee commitment, completion of the work, the performance of employees